2022
DOI: 10.1093/braincomms/fcad013
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative delirium is associated with grey matter brain volume loss

Abstract: Delirium is associated with long-term cognitive dysfunction and with increased brain atrophy. However, it is unclear whether these problems result from or predispose to delirium. We aimed to investigate preoperative to postoperative brain changes, as well as the role of delirium in these changes over time. We investigated the effects of surgery and postoperative delirium with brain MRIs made before and three months after major elective surgery in 299 elderly patients, and an MRI with a three mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…We have shown that episodes of POD might be detrimental for white matter integrity. Together with the loss of gray matter volume after episodes of POD, 36 our findings could represent the structural correlate of worsening cognitive trajectories in POD patients. 37 Future studies need to investigate whether this white and gray matter depletion after episodes of delirium may lead to cognitive decline and eventually the development of dementia.…”
Section: Discussionsupporting
confidence: 55%
“…We have shown that episodes of POD might be detrimental for white matter integrity. Together with the loss of gray matter volume after episodes of POD, 36 our findings could represent the structural correlate of worsening cognitive trajectories in POD patients. 37 Future studies need to investigate whether this white and gray matter depletion after episodes of delirium may lead to cognitive decline and eventually the development of dementia.…”
Section: Discussionsupporting
confidence: 55%
“…impaired blood flow and tissue perfusion). These pathways may contribute to increased progression of grey matter volume loss and long-lasting decreased brain functional connectivity that were observed after delirium [45 ▪ ,46 ▪ ].…”
Section: Dementiamentioning
confidence: 99%
“…20,21 Preoperative cortical brain infarcts, complex white matter hyperintensity, brain atrophy, and glymphatic system changes are examples of brain areas that could be used as surrogate markers for brain vulnerability. 22,23 In addition, hypointense areas in the cholinergic system were related to POD, possibly representing areas of iron deposition and calcifications, also seen in a range of neurodegenerative diseases. 24 Challenges such as diagnostic assessment method, frequency of evaluation, and constraints related to the collection of biomarkers all make this task difficult.…”
Section: Promising Biomarkersmentioning
confidence: 99%
“…Other promising biomarkers relate to imaging studies, some of which have identified specific brain lesions that might predispose at-risk populations for developing POD 20,21 . Preoperative cortical brain infarcts, complex white matter hyperintensity, brain atrophy, and glymphatic system changes are examples of brain areas that could be used as surrogate markers for brain vulnerability 22,23 . In addition, hypointense areas in the cholinergic system were related to POD, possibly representing areas of iron deposition and calcifications, also seen in a range of neurodegenerative diseases 24 …”
Section: Current Evidencementioning
confidence: 99%